2010
DOI: 10.1124/dmd.110.035378
|View full text |Cite
|
Sign up to set email alerts
|

CYP4F Enzymes Are Responsible for the Elimination of Fingolimod (FTY720), a Novel Treatment of Relapsing Multiple Sclerosis

Abstract: CYP4F2 with an IC 50 of 1.6 M), whereas there was only a slight inhibition found with azamulin and none with troleandomycin. An antibody against CYP4F2 was able to inhibit the metabolism of fingolimod almost completely in HLM, whereas antibodies specific to CYP2D6, CYP2E1, and CYP3A4 did not show significant inhibition. Combining the results of these four enzyme phenotyping approaches, we demonstrated that CYP4F2 and possibly other enzymes of the CYP4F subfamily (e.g., CYP4F3B) are the major enzymes responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…Its elimination occurs primarily by hydroxylation mediated by CYP4F2 and possibly other enzymes of the CYP4F subfamily. Although -hydroxylated fingolimod was the major biotransformation product observed, six other metabolites with internal hydroxylations were identified (53). This goes along with our identification of multiple isomers of both 1-deoxySO-OH and 1-deoxySA-2OH.…”
Section: The Downstream Metabolism Of 1-deoxyso Is Mediated By Cyp4fsupporting
confidence: 53%
See 1 more Smart Citation
“…Its elimination occurs primarily by hydroxylation mediated by CYP4F2 and possibly other enzymes of the CYP4F subfamily. Although -hydroxylated fingolimod was the major biotransformation product observed, six other metabolites with internal hydroxylations were identified (53). This goes along with our identification of multiple isomers of both 1-deoxySO-OH and 1-deoxySA-2OH.…”
Section: The Downstream Metabolism Of 1-deoxyso Is Mediated By Cyp4fsupporting
confidence: 53%
“…CYP4F enzymes have been shown to mediate the degradation of fingolimod (FTY720), an S1P analog used in treating relapsing multiple sclerosis (53). Its elimination occurs primarily by hydroxylation mediated by CYP4F2 and possibly other enzymes of the CYP4F subfamily.…”
Section: The Downstream Metabolism Of 1-deoxyso Is Mediated By Cyp4fmentioning
confidence: 99%
“…In addition, P450 4F12 reportedly metabolizes a number of antiallergy drugs, including ebastine, astemizole, and terfenadine (Hashizume et al, 2002;Eksterowicz et al, 2014). P450 4F2 and/or 4F3B also are responsible for the O-demethylation of the antiparasitic prodrug pafuramidine and the v-hydroxylation of fingolimod, an oral drug for relapsing multiple sclerosis (Wang et al, 2007;Jin et al, 2011). These findings suggest that P450 4F enzymes are responsible for endogenous and xenobiotic biotransformations.…”
Section: Introductionmentioning
confidence: 78%
“…Indeed, O-demethylation of pafuramidine in human intestine microsomes reportedly inhibited 92% of total metabolic activity by anti-P450 4F2 antibodies, whereas the antibodies against P450 3A4/5 and 2J2 showed moderate inhibition (approximately 28%). In addition, P450 4F2 and/or 4F3B enzymes reportedly catalyzed v-hydroxylation of fingolimod, the major elimination pathway (Jin et al, 2011). v-Hydroxylation of fingolimod in human liver microsomes also inhibited 93% of total metabolic activity by anti-P450 4F2 antibodies, differing from little or no effects by antibodies of P450 2D6, 2E1, and 3A4.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies with human liver microsomes and animal studies have shown that cytochrome P450 (CYP) 4F2 and other enzymes of the CYP4F subfamily, with a minor contribution reported from other CYP enzymes, are largely responsible for the oxidative metabolism and the subsequent elimination of FTY (Jin et al., 2011; Kalsotra, Anakk, Boehme, & Strobel, 2002; Kovarik et al., 2005, 2006; Wang & Strobel, 1997; Waxman, Ram, Pampori, & Shapiro, 1995; Zimmerlin & Patten, 2000). Sex‐dependent expression of cytochromes P450 and their influence on drug metabolism and drug toxicity have been previously reported.…”
Section: Resultsmentioning
confidence: 99%